Creatures of Fashion: Animals, Global Markets, and the Transformation of Patagonia by John Soluri. Chapel Hill: University of North Carolina Press. 2024. 272 pp. $27.95 (pbk); $99.00 (hbk); $21.99 (e-book). ISBN: 978-1-4696-7572-5; ISBN: 97814696-7571-8; ISBN: 97814696-7573-2 - Ejarque, Mercedes (Wiley, 2025)
Desert … remoteness … the end of the world … are some of the ways in which the history of the Patagonian region, in the extreme south of the American continent, has been characterised. In recent decades, this narrative has been challenged and reinterpreted by a new generation of regional historians employing diverse approaches and analytical perspectives. These scholars have endeavoured to transcend geographical and political boundaries, integrate the historical processes of the region with global dynamics, contextualise the narratives of individual and family biographies within the dominant social groups and recognise and value the presence of indigenous populations in the construction of social history (Bandieri 2021; López and Gattica 2000). Likewise, Patagonia has been the focus of an increasing number of studies that seek to transcend the conventional boundaries of agrarian history, with the aim of (re)constructing an environmental history that examines the intricate relationships and conflicts between production and the exploitation of nature (Andrade 2003; Blanco and Mendes 2006; Ejarque 2014; Haller 2023).